2009
DOI: 10.1103/physrevb.79.241309
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear cyclotron resonance of a massless quasiparticle in graphene

Abstract: We consider the classical motion of a massless quasi-particle in a magnetic field and under a weak electromagnetic radiation with the frequency ω. Due to the non-parabolic, linear energy dispersion, the particle responds not only at the frequency ω but generates a broad frequency spectrum around it. The linewidth of the cyclotron resonance turns out to be very broad even in a perfectly pure material which allows one to explain recent experimental data in graphene. It is concluded that the linear response theor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…Nonlinear cyclotron resonance in graphene was considered theoretically in [5], again in the classical limit, by solving the equation of motion F = dp/dt for a massless charge. Classical approximation can be applied to electrons in low magnetic field that are occupying highly excited Landau levels n 1, when energy and momentum quantization are neglected.…”
mentioning
confidence: 99%
“…Nonlinear cyclotron resonance in graphene was considered theoretically in [5], again in the classical limit, by solving the equation of motion F = dp/dt for a massless charge. Classical approximation can be applied to electrons in low magnetic field that are occupying highly excited Landau levels n 1, when energy and momentum quantization are neglected.…”
mentioning
confidence: 99%
“…[1][2][3] While a number of electronic transport studies have revealed novel phenomena in the presence of a high magnetic field, including half-integer quantum Hall states observed at room temperature, 1,2,4 magneto-optical properties are expected to be equally unusual, [5][6][7][8][9][10][11][12][13][14][15] especially in the magnetic quantum limit 12 where the Fermi level resides in the lowest Landau level (LL). Even in conventional 2D electron systems such as found in GaAs quantum wells, studies of cyclotron resonance (CR) in the magnetic quantum limit have shown many-body effects, [16][17][18][19] such as spin splitting in the fractional quantum Hall regime, even though CR is not expected to be sensitive to electron-electron interactions due to Kohn's theorem.…”
mentioning
confidence: 99%
“…This fact was theoretically discussed in [31], where it was shown that the EM response linear theory is inapplicable to describe cyclotron absorption in zero band gap graphene.…”
Section: Introductionmentioning
confidence: 93%